A PERSPECTIVE ON IMPORT AND EXPORT OF DRUGS- PROCESSOR ASPECTS - challabathula, Dr.subha kumar (IJRDO - Journal of Social Science and Humanities Research, 2018)
Liberalization measures in the pharmaceutical sector have brought about major changes in the industrial licensing policy; Exports of formulations have grown faster while their imports have not registered any jump, keeping the balance of trade positive. But there has been a decline in domestic production of bulk drugs and a growth in imports because the industry is moving away from intermediates and is focusing on bulk drugs at the high end of the value chain.